Development of Specialization Selection on The Job Training for Human Resources in The Hospitality Industry through E-OJTKU - Dima, Cindy Citya; Izza, Dedi Joko Purnomo; Asshofi, Ulumuddin Ahmad; Pranatha, Prima Setia Judha (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
The previous problem in this research was exploring the potential of students in choosing departments in hotels, namely front office, housekeeping, and food and beverage to carry out internships. The need for this selection recommendation is based not only on student desires or the availability of opportunities to learn to work in the existing hotel industry but also based on recommended grades from semesters 1 to 3 which fulfill the requirements for industrial internships. This research uses a qualitative descriptive method with a case study approach. Data collection techniques through observation, interviews and document study. Interviews use a semi-structured model so that answers are open-ended and can be developed for in-depth analysis. E-ojtku is an innovation resulting from research based website and android to improve the competency of Hospitality Management students who received recognition for 40 credits for OJT 1 and OJT 2 (1 year in industry / Hotels) for a career in Hotels. The test results using e-ojtku obtained good results with an accuracy of up to 94.44% with a ratio of 80% training data and 20% test data, the ratio of the amount of training data can affect the accuracy of the values in each experiment.